PENGARUH ASSET STRUCTURE, ASSET QUALITY, CAPITALIZATION, SIZE TERHADAP RETURN ON ASSET PADA PERUSAHAAN PERBANKAN - Ariyanti, Rizka (JURNAL LITBANG KOTA PEKALONGAN, 2017)
This study aims to examine and analyze Return On Assets (Studies in Bank Go Public in Indonesia Stock Exchange 2011-2015). To test these variables, the researchers use the 25 companies that went public in Indonesia Stock Exchange. This type of research is explanatory research. The data used in this research are secondary data from financial statements published by banking companies during 2011-2015. Furthermore, the data collected was analyzed quantitatively using multiple regressi using Eviews program version 8.1. Silmultan The results showed that the variable asset structure, asset quality, capitalization, and size affect Return On Assets (ROA). Indicate that the asset structure is not significant negative on Return On Assets (ROA), variable asset quality significantly negative on financial Return On Assets, variable capitalization significant positive effect on Return On Assets, variable size significantly influence Return On Asset (ROA),